2013
DOI: 10.1637/10518-022213-resnote.1
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Two Trichomonas gallinae Isolates in Chlorinated and Distilled Water With or Without Organic Material

Abstract: Trichomonas gallinae is a protozoan parasite commonly found in columbids, passerines, and raptors. In passerines and columbids, trichomonosis causes significant morbidity and mortality associated with contaminated bird feeders and waters. However, there has been little work on the persistence of T. gallinae in water to determine if artificial waters are a likely source of infection for naive birds. To examine drinking water as a source of T. gallinae transmission, we inoculated 1 x 10(6) trichomonads into cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…Additionally, given recent prevalence and transmission data it seems unlikely that transmission from non-human hosts represents a significant proportion of infections. Contaminated surfaces and water [83], uncooked meat, or direct contact with pets and farm animals could lead to animal-to-human transmissions of trichomonads. Initial infections were presumably through the digestive tract (via oral ingestion) with further progression to the lungs for some (various) species or the urogenital tract (T. vaginalis).…”
Section: Investigating Trichomonads As Emerging Infectious Diseases Amentioning
confidence: 99%
“…Additionally, given recent prevalence and transmission data it seems unlikely that transmission from non-human hosts represents a significant proportion of infections. Contaminated surfaces and water [83], uncooked meat, or direct contact with pets and farm animals could lead to animal-to-human transmissions of trichomonads. Initial infections were presumably through the digestive tract (via oral ingestion) with further progression to the lungs for some (various) species or the urogenital tract (T. vaginalis).…”
Section: Investigating Trichomonads As Emerging Infectious Diseases Amentioning
confidence: 99%
“…In the present study, T. gallinae was not detected in water collected from sites where trichomonosis mortalities were occurring. This was surprising given that Bunbury et al (2007) were successful in recovering T. gallinae from puddles and Gerhold et al (2013) found that T. gallinae was able to survive for up to 20 minutes in both distilled and chlorinated water when organic matter (detritus, leaves and soil) was present. One caveat to our water sampling success was that property owners undergoing bird mortalities in their backyards became more diligent in cleaning feeders and waterers.…”
Section: Discussionmentioning
confidence: 99%
“…The main route of transmission of T . gallinae between birds includes the feeding of squabs by an adult, normal feeding via courtship billing during nesting, sharing contaminated food or water sources, and via predation and necrophagy from raptors in the wild [ 9 , 10 ]. Trichomonas gallinae in captive falcons in Saudi Arabia and Middle East seem to be related to the traditional Arabian falconry practices of training falcons using live or freshly domestic pigeons [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%